Wine science : principles and applications - Jackson, Ron S. (Academic Press, 2020)
Wine Science: Principles and Applications, Fifth Edition, delivers in-depth information and expertise in a single, science-focused volume, including all the complexities and nuances of creating a quality wine product. From variety, to the chemistry that transforms grape to fruit to wine, the book presents sections on the most important information regarding wine laws, authentication, the latest technology used in wine production, and expert-insights into the sensory appreciation of wine and its implications in health. This book is ideal for anyone seeking to understand the science that produces quality wines of every type.